1975
DOI: 10.1038/bjc.1975.243
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by prolactin of carcinogen induced mammary cancerigenesis in the male rat

Abstract: Summary.-Mammary tumours were induced in 3 groups of male Long-Evans rats by a series of 6 fortnightly gastric intubations of 7, 12-dimethylbenzanthracene. Two weeks before the initial carcinogen treatment one group of rats was grafted with 3 pituitary homografts underneath the kidney capsule of each recipient (hyperprolactinaemia). A second group, 2 weeks before the initial carcinogen treatment and for the duration of the study (35 weeks), were injected 4x weekly with 2-Br-oaergocryptine (CB-154) (hypoprolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Cisplatin is a platinum-based chemotherapeutic agent that has been used to decrease experimentally induced tumor development in the mammary glands of rats in models of human breast cancer. 10,43 In the present study, only 1 rat received intralesional cisplatin, and we cannot draw any conclusions regarding its effectiveness.…”
Section: Small Animals and Exoticmentioning
confidence: 73%
See 1 more Smart Citation
“…Cisplatin is a platinum-based chemotherapeutic agent that has been used to decrease experimentally induced tumor development in the mammary glands of rats in models of human breast cancer. 10,43 In the present study, only 1 rat received intralesional cisplatin, and we cannot draw any conclusions regarding its effectiveness.…”
Section: Small Animals and Exoticmentioning
confidence: 73%
“…Mammary gland fibroadenomas are associated with prolactinemia in some strains of laboratory rats. [8][9][10][11] Prolactin secretion increases subsequent to a decrease in the secretion of dopamine from the pituitary gland in geriatric rats 12 and persistent low concentrations of progesterone, constant estrus, or cessation of ovulation in female rats. 7,13,14 In some laboratory rat strains, including the Sprague-Dawley, 12 Fisher, 15 and Wistar 16,17 strains, pituitary gland adenomas develop in > 80% of rats > 24 months old.…”
Section: Small Animals and Exoticmentioning
confidence: 99%
“…Experimental studies have reported that PRL induces proliferation of breast cancer cells in vitro and enhances growth of mammary carcinoma in rodents and may act as an autocrine or paracrine factor within mammary tissue (5,6). Furthermore, several case reports of breast carcinomas in women and men with prolactinomas have been reported (7)(8)(9) raising the issue of whether high PRL levels are associated with an increased risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of rat Prl using the lipocalin promoter to drive expression predominantly in mammary epithelium produces (ER) positive tumors at a higher rate than other mouse mammary cancer models (Rose-Hellekant et al, 2003). Prl as a modulator of preinitiated cancer has been examined in chemical carcinogenesis (Welsch et al, 1975) and transgenic oncogene models. Prl and Prlr mRNA were detected in nitrosomethylurea (NMU) carcinogeninduced tumors and a rat Prl antiserum inhibited NMU-induced tumor cell proliferation by up to 70%, compared to normal rabbit serum and GH antiserum (Mershon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%